Theoretical and experimental investigations of the 2-(4-chlorophenyl)-3-{[5-(2-cyano-2-phenylethenyl)]furan-2-yl}acrylonitrile molecule as a potential acceptor in organic solar cells - Kazici, Mehmet; Bozar, Sinem; Yuksel, Sureyya Aydin; Ongul, Fatih; Gokce, Halil; Gunes, Serap; Goreci, Cigdem Yorur (IOP Publishing Ltd, 2016)
A novel soluble asymmetric acrylonitrile derivative, 2-(4-Chlorophenyl)-3-{[5-(2-cyano-2-phenylethenyl)]furan-2-yl}acrylonitrile (CPCPFA, 3) was synthesized in three steps by Knoevenagel condensation. The structure of the CPCPFA was characterized using UV-vis, FTIR, H-1 NMR, C-13 NMR, and LC-MS. CPCPFA was evaluated as an electron acceptor in bulk heterojunction organic solar cells. Its optical and electronic properties as well as photovoltaic performance were investigated.
Keywords: acrylonitriles; Knoevenagel condensation; organic solar cells; acceptor type molecules; BULK-HETEROJUNCTION; OPTICAL-PROPERTIES; NON-FULLERENE; POLYMER; SEMICONDUCTORS; CONVERSION; DESIGN; Science & Technology - Other Topics; Materials Science; Physics